MOTHER'S KNOWLEDGE ABOUT NUTRITION WITH BEHAVIOR OF FEEDING IN PUSKESMAS BOTTANIA BATAM CITY - Mohd Faisyal Reza; Efilona Setri (Universitas Batam, 2021)
Nutritional problems are a complex problem not only due to powerlessness or economic inadequacy, but also regarding knowledge, attitudes and behavior. The practice of giving food to infants and children, especially at the age of 0–23 months, must be carried out correctly and appropriately. Feeding errors in this period can lead to malnutrition and stunting. The purpose of this study was to determine the knowledge of mothers about nutrition with feeding behavior in toddlers. Method :The research method used was an analytic survey with a cross sectional approach. Conducted at Botania puskesmas, the study was conducted for 6 months, the population in this study were toddlers' mothers who came to the Botania puskesmas. The sample in this study was 40 people. The sampling technique was carried out by accidental sampling technique with research instruments using a questionnaire. Data analysis using Chi square. Result : The results of the research on maternal knowledge about good toddler nutrition were equal to the frequency of maternal knowledge about adequate nutrition, namely (20) respondents (50%), the majority of toddlers' feeding behavior was good (22) toddlers (55%). Chi-square statistical test obtained p-value = 0.00 <0.05, Conclusion : there is a significant relationship between maternal knowledge about nutrition and feeding behavior of children under five at Botania Health Center. Suggestions that the authors provide to provide health education, especially nutrition for toddlers.